Gambaran Lingkungan Kerja terhadap Perilaku Tidak Aman pada Pekerja di Pabrik Tahu Tempe XYZ - Richo Roshelio Tiao; Nur Hafizah Cantika Putri; Zefanya Emmanuela Simanjuntak; Radja Nikra Achmad; Anis Rohmana Malik; Andhika Aryaputra; Reginal Octavianus J Baggy; Ilham Nurul Hikmah (Pusat riset dan Inovasi Nasional, 2025)
Small-scale industries such as tofu and tempeh factories play a significant role in the local economy but often face serious issues such as workplace accidents. This study aims to describe the working conditions and their relation to unsafe acts by workers at the XYZ tofu and tempeh factory. A descriptive qualitative approach was used through direct observation and interviews with four workers. The findings show that a hot and noisy work environment, poor ventilation, and disorganized workspace affect workers’ behavior in carrying out tasks without using proper personal protective equipment (PPE). Unsafe work practices have become a common habit due to factors such as routine behavior, limited facilities, and demands for work efficiency. The study concludes that an unsupportive work environment is directly associated with the increase in unsafe behavior. Therefore, efforts are needed to improve the working environment, including ventilation, workspace layout, and adequate provision of PPE, as well as to increase workers’ awareness of occupational health and safety through regular training and outreach. These measures are essential to foster a safe and healthy work culture in small-scale industrial settings.